The effects of social change on the status and role of the elderly within the Algerian family - AMEZIANE, Naima (Social Sciences Journal)
In this article, we tried to clarify the developments that affected the behavior within the Algerian family, as well as the view of the new generation towards the elderly group. We also tried to clarify the outcomes of social change on the status and role of this group. And the conclusion reached confirms that modernity and urbanization have played a major role in the qualitative shift of the Algerian family from the extended model to the nuclear model, and it has been concluded that this new model has resigned from some of its duties towards its members in favor of some social institutions.